Carbon Estimation in Mangrove Forests of The East Coast of North Sumatra - Bambang Hendra Siswoyo; Siti Mardiana; Raja Sabrina (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Mangrove forests are important ecosystems, providing various ecological, economic, and social benefits. They serve as habitats for a wide range of species, act as natural barriers against coastal erosion, and play a key role in carbon sequestration, which helps to reduce the impacts of climate change. This study used surveys to tree biomass growth and quantify the carbon stocks trapped in this ecosystem. The methodology applied in measuring carbon in mangrove forests is similar to that used in primary forests, although some unique aspects need to be considered, such as the accumulation of non-biodegradable debris. Aspects that need to be considered, such as litter accumulation cannot be included in technical carbon calculations. included in technical carbon calculations. The condition of mangrove forests in North Sumatra shows a significant decline, with a 61.21% significant decline, with a in primary mangrove area between 1990 to 2015, mainly due to land conversion for aquaculture and agriculture. Carbon sequestration in mangrove forests is crucial to mitigating climate change, with their capacity to store carbon in biomass and sediment. Rehabilitation efforts, such as propagation planting and seedlings, showed expected survival rates and large carbon storage potential, with total carbon stocks reaching 558.07 mgC ha-1. It is important to understand carbon storage dynamics and influencing factors, such as duration and nutrient inputs, for effective management and conservation strategies